EXERCISE ACTIVITY AND MOTIVATION AMONG MEDICAL STUDENTS: A CROSS-SECTIONAL STUDY FROM INDONESIA - Sylviana, Nova; Karisa, Putri; Padantyasari, Aldia Maharani; Pratiwi, Yuni Susanti; Setiawan, Setiawan (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2026)
Background: Medical students are at a critical stage of life, facing intense academic, psychological, and social demands. Regular exercise can support physical and mental well-being. However, physical inactivity remains a common issue among university students, particularly those in demanding academic environments. Aims: This study aimed to examine exercise activity, motivational profiles, and their associations among medical students.Methods: A cross-sectional study was conducted in October 2020 using an online survey among undergraduate medical students at Universitas Padjadjaran, Indonesia (n = 651). Physical activity was measured using the Godin Leisure-Time Exercise Questionnaire (GLTEQ), and motivational regulation was assessed using the Behavioral Regulation in Exercise Questionnaire-3 (BREQ-3). Non-parametric tests and Spearman correlations were applied to analyze group differences and associations.Results: Although 89.7% of participants reported engaging in exercise, only 31.5% met recommended physical activity levels, with 68.5% classified as insufficiently active. Identified regulation showed the highest median score, followed by intrinsic and integrated regulation, indicating a predominance of autonomous motivation. Active students demonstrated significantly higher intrinsic, integrated, and identified regulation compared to insufficiently active students (p < 0.001). Integrated regulation showed the strongest positive correlation with GLTEQ-METS (r = 0.451), while amotivation was negatively correlated (r = –0.192, p < 0.01). Male students were more likely than female students to meet recommended activity levels (p = 0.001).Conclusions: Despite relatively strong autonomous motivation, most medical students did not achieve recommended physical activity levels, suggesting an intention-behaviour gap influenced by contextual and structural factors. These findings highlight the need for institutional strategies within medical education to support sustainable physical activity behaviors and promote student well-being.